Generación de innovaciones para mejorar la competitividad y los beneficios de los actores - Jäger, M.; Amaya, K. (2014)
This publication shows how the project ”Rescue and Promotion of Native Chilies in their Centre of Origin” facilitated the generation of commercial, institutional and technological innovations enhancing the competitivity and the benefits of the actors of the native chilies value chain in Bolivia and Peru